Smitten "The most fun dating app in Europe" : Marketing Plan for the German Market - Darri Logi Skúlason 1995- (2022)
The goal of this research was to create a marketing plan that Smitten can benefit from when entering the German market. Smitten is an Icelandic startup that was launched in Iceland in 2019. It quickly became the most popular dating app in its home market. They aim to become a strong player in the global market in the dating service industry. They have spotted a gap in the market and offer more fun and playful dating experiences for their target market, Generation Z. In the beginning the author describes the history of Smitten, what it stands for and how they have succeeded in their markets. Their differentiation on the market, their vision and plans are reviewed. Their success in Iceland has been exceptionally good. They have already started to expand into the Danish market and today the outlook is very positive that they will gain a foothold in Denmark. They have gone through two rounds of funding and the third is underway. Smitten intends to enter into more markets in the coming months, one of them is Germany. In this study, the aim is to draw up a marketing plan for the company if it intends to enter the German market in the coming months. This research will cover the seven important steps that companies need to take when preparing a marketing plan. In the discussion of each level, the theoretical part will be linked to Smitten's actions. Analytical tools such as SWOT will be used, which is a critical conclusion about the main strengths, weaknesses of the internal environment and then PESTLE which analyzes the external environment into threats and opportunities in the German market. Porter's five key points will be considered when analyzing competitors in the market. Then the Ansoff interest rate model will be used. Dating Apps that are trying to scale to a new market often have a difficult time getting users to sign up and start using them. This is known as the Cold Start Problem, and it will be discussed in more detail in this research.There are many indications that Smitten is doing good things and that ...